How the Bible Works Russian Baptist Faith as Text - Mikeshin, Igor (2021)
This article is about Russian Baptists' perception of their faith as a text. I argue that they practice their lived faith by interiorizing the language of the Russian Synodal Translation of the Bible as their "language of reasoning". I support this claim by analyzing two aspects of faith: as an act of conversion and as a process of living a Christian life. To illustrate the mechanism of sustaining faith, I use the case of a rehabilitation ministry for addicted people to unpack narratives of conversion, gender order, and family life. Biblical literalism is the basis of the Russian Baptist faith narrative, and in this article I scrutinize the mechanism of its construction.
Keywords: Bible; Conversion; Faith; family values; gender order; language of reasoning; Russian Baptists